2019
DOI: 10.5761/atcs.oa.18-00309
|View full text |Cite
|
Sign up to set email alerts
|

Cone Type Repair Has Become Our First Option in the Treatment of Adult Ebstein Anomaly

Abstract: Purpose: Different surgical procedures were defined due to degree of Ebstein anomaly. In this study, we are reporting our surgical experience of adult patients with Ebstein anomaly.Methods: We analyzed the patients, who had operated with the diagnosis of Ebstein anomaly from March 2011 through February 2018, retrospectively. We evaluated patients in two groups: patients with cone type surgical repair were in Group 1 and patients with other surgical (Danielson, Carpentier) procedures were in Group 2.Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Our series redemonstrates the excellent long-term overall survival of patients undergoing cone repair, in keeping with other large institutions. 3 , 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 We showed excellent long-term survival with no early or late mortalities in our cohort. Additionally, we demonstrated acceptable levels of TR that remained stable over time and the feasibility of using annuloplasty rings as a protective measure without increasing the risk of TS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our series redemonstrates the excellent long-term overall survival of patients undergoing cone repair, in keeping with other large institutions. 3 , 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 We showed excellent long-term survival with no early or late mortalities in our cohort. Additionally, we demonstrated acceptable levels of TR that remained stable over time and the feasibility of using annuloplasty rings as a protective measure without increasing the risk of TS.…”
Section: Discussionsupporting
confidence: 55%
“…Short- and midterm results at global major institutions using the cone repair technique have shown uniformly positive results with low morbidity and mortality. 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 However, long-term outcomes for the cone repair are still needed, and questions remain surrounding the effect of the cone repair on biventricular function and remodeling, valve durability, and echocardiographic follow-up with regard to residual and recurrent TR. 8 , 15 , 21 Of note, predictors of reoperation among those undergoing cone repair compared with those undergoing TVR are as yet unelucidated, and there are relatively few studies comparing midterm outcomes between cone repair and TVR.…”
mentioning
confidence: 99%
“…They found that the cone repair provided a higher rate of successful repair and a lower rate of moderate/severe TR ( p = 0.03). Ozbek and his associates ( 12 ) reached a similar conclusion that the rate of moderate/severe TR of cone repair was lower than other repairs in patients with EA postoperatively ( p = 0.009). Vogel et al ( 20 ) found that the cone repair had a higher rate of reduction in TR than conventional surgery in patients with EA ( p = 0.004).…”
Section: Discussionmentioning
confidence: 65%
“…Different surgical interventions are defined due to leaflet hypoplasia and the degree of cardiac malformation. TV repair, TV replacement, ventricular plication, ASD closure, bidirectional cavopulmonary shunt (BCPS), and cryoablation are the most common surgical procedures ( 12 ). When technically feasible, repair of the TV is usually preferable to replacement ( 9 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation